Consumer Protection For Credit Card Holders Against Transaction Bills Not Made By Customers Perspective Fatwa Dsn Mui Number 54/Dsn/Mui/X/2006 - Ritonga, Nadiyah Roihanah; Zahara, Fatimah (UNIVERSITAS PAKUAN, 2025)
The development of digital financial technology has brought ease of transactions, but also increased the risk of credit card misuse, especially illegal transactions that are not carried out by customers. This study aims to find out the normative review of consumer protection regulations in the financial services sector (banks), to analyze the DSN-MUI fatwa on unauthorized transactions and forms of customer protection, to find out the form of protection provided by banks to credit card users, and, to find out the form of responsibility of banks for illegal transactions experienced by customers. This type of research is juridical-normative with a conceptual approach and a statute approach. Data is collected through document studies and then data is processed qualitatively and analyzed using deductive logic. The results of the study show that banks have an absolute responsibility in ensuring the security of the transaction system and are obliged to provide protection to customers. The DSN-MUI fatwa emphasizes the importance of a valid contract and the principle of justice, which prohibits the imposition of losses on customers for transactions without consent. Real cases such as credit card break-ins by third parties show the weakness of banks' verification systems and digital security. Therefore, customer protection needs to be carried out through preventive (such as improving consumer security and education systems) and repressive approaches (such as compensation and administrative sanctions). This study emphasizes the importance of collaboration between positive law and sharia principles in protecting consumers for transactions made from credit card holders so that transactions do not occur without customer consent